Enrichment Factor and Chemical Composition of Size Separated Airborne Particulate Matter of Singrauli Coalfield, India - Yadav A.K.; Sahoo S.K.; Patra A.C.; Thakur V.K.; Dubey J.S.; Singh S.; Lenka P.; Jha V.; Kumar A.V.; Shirin S.; Jamal A. (My University, 2025)
A sequential extraction guideline and protocol procedures were applied to specify and analyze major and trace elements, and water-soluble inorganic ions in size-separated atmosphere particulate matter. Quality control and quality of analysis were assured using standard reference materials and standards like NIST, USA. Enrichment of various elements was estimated. The enrichment factor of Co, Cu, Br, As, Zn, and H were found to be 5–150, indicating that these elements originate from sources of anthropogenic emission. A higher enrichment factor of N and Se in PM2.5 was also observed and can be attributed to industrial sources such as coal-related industry and coal storage areas near the monitoring station. The high correlation of NO3− with Cl−, F−, NO2−, SO42−, and Mg2+ indicates that these ions are likely to be originating from the same source, such as biomass burning. © 2022, The Author(s) under exclusive licence to Institute of Earth Environment, Chinese Academy Sciences.